103 QIP: implementing a palliative care electronic patient profile to improve mdt communication and handover. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Richardson, Fiona
Abstract : Background and Introduction: Northumbria Healthcare Trust uses an electronic patient record called 'Nervecentre' to display admission information. This was often inaccurate and less palliative care focussed. A palliative care profile ('PCU Profile') was created within this software with the aim to improve information sharing and handover. Methods: Usage of 'Nervecentre' and the data within the current 'Medical Profile' were analysed in terms of accuracy and inclusion of palliative care specific outcome measures (phase of illness and Australia-modified Karnofsky Performance Status (AKPS)). Qualitative data was gathered on the current weekend handover process (junior doctors creating a document every Friday). The 'PCU Profile' included relevant information about the patient's admission with designated areas for weekend handover. The MDT completed and edited the profile during the hospital admission. After implementation, the accuracy of the data included was reviewed and feedback gained. Results: 45 'Medical profiles' were analysed which included 19 inpatients over 10 days. None of these profiles had phase of illness or AKPS documented. All included the correct resuscitation status. The diagnosis was accurate in 67% with an updated management plan in 29%. 58% had the correct past medical history. With regards to weekend handover, a move to using 'Nervecentre' was supported with current issues including reliability, clinical governance and efficiency. The 'PCU Profile' led to 91% of diagnoses being accurate, 100% of management plans updated, 82% of profiles stating AKPS and 91% including phase of illness. Quantitative feedback is ongoing but has been positive especially with regards to weekend handover. Conclusions: Initial data shows improved accuracy of inpatient information leading to more efficient, accurate and therefore safer verbal handovers thus improving patient care. Virtual handover to the on-call team improved ease of information sharing, confidentiality and patient safety. It is hoped more feedback will allow the profile to evolve in future.